Papadopoulou, Maria - (:unkn) unknown (My University, 2026)
Maria Papadopoulou is an assistant professor at the Department of Nursing (2008-2015), leading midwifery education, a postgraduate, post-nursing program. She holds a Diploma in Nursing and in Midwifery, a BSc (Hons) in Nursing and Midwifery Education from the Anglia Polytechnic University, UK and a Master degree in Public Sector Management from the Cyprus International Institute of Management (2009). She has previous teaching experience as a Nursing and Midwifery tutor at the School of Nursing and Midwifery since 1990 to 2007 and previous clinical experience as a clinical nurse and midwife since 1983 to 1990. Her research interests focus on quality of midwifery education and practice and professional capacity building. She contributed to the profession as elected Board Member of the Nursing and Midwifery Council, the Cyprus Nurses and Midwives Association, and the International Confederation of Midwives.